2008
DOI: 10.5713/ajas.2008.70035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Fish Oil on Semen Quality of Goats

Abstract: The aim of the study was to investigate the effect of dietary fish oil supplementation on the semen characteristics of the Markhoz buck. Sixteen bucks were randomly allocated into 4 groups and received four different diets: unsupplemented control diet, supplemented with fish oil at 2.50% dry matter (DM), supplemented with fish oil (2.50% DM) and vitamin E (0.30 g/kg DM), and supplemented with vitamin E (0.30 g/kg DM). All experimental diets were formulated according to AFRC (1998). Semen was collected at 14 d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 24 publications
8
31
0
1
Order By: Relevance
“…Increasing PUFA sources in the diet resulted in a concomitant increase in n-3 fatty acids of sperm lipid and semen quality in boars (Rooke et al, 2001;Mitre et al, 2004) cockerels and stallions (Brinsko et al, 2005). Furthermore, we recently reported that dietary fish oil supplementation improved the total number and sperm concentration, motility and progressive motility of goat sperm during the non-breeding season (Dolatpanah et al, 2008). In contrast, other studies (Paulenz et al, 1999;Blesbois et al, 2004) reported no effect of dietary fish oil supplementation on sperm motility in various animal species.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Increasing PUFA sources in the diet resulted in a concomitant increase in n-3 fatty acids of sperm lipid and semen quality in boars (Rooke et al, 2001;Mitre et al, 2004) cockerels and stallions (Brinsko et al, 2005). Furthermore, we recently reported that dietary fish oil supplementation improved the total number and sperm concentration, motility and progressive motility of goat sperm during the non-breeding season (Dolatpanah et al, 2008). In contrast, other studies (Paulenz et al, 1999;Blesbois et al, 2004) reported no effect of dietary fish oil supplementation on sperm motility in various animal species.…”
Section: Discussionmentioning
confidence: 69%
“…Feeding PUFAs increased sperm lipid content in several species (Mitre et al, 2004;Zaniboni et al, 2006); fish oil as a source of n-3 fatty acids improved the semen quality in goats (Dolatpanah et al, 2008), boars (Rooke et al, 2001) and turkeys . However, there are apparently no reports regarding the effects of fish oil supplementation on the semen characteristics and sperm lipid composition of rams.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with the results of Gholami (Gholami et al., ) in bull, Zaniboni in turkey (Zaniboni et al., ), Mourvaki in rabbit (Mourvaki, Cardinali, Dal Bosco, Corazzi, & Castellini, ) and Adeel in Nili‐Ravi buffalo bulls (Adeel et al., ) those who investigated various dietary PUFAs supplementation. In contrast, studies in ram (Esmaeili, Shahverdi, Alizadeh, Alipour, & Chehrazi, ; Samadian et al., ), goat (Dolatpanah et al., ), chicken (Cerolini et al., ) and boar (Estienne et al., ) found evidence of a positive effect of dietary PUFAs supplementation on semen characteristics. The possible mechanisms by which PUFAs affect semen characteristics are not well understood, and further studies are needed to determine them.…”
Section: Discussionmentioning
confidence: 95%
“…Although it has been shown that dietary supplementation with a wide range of PUFA supplements can alter fatty acid profile and characteristics of spermatozoa, there are opposing results on the effect of PUFAs on fresh and frozen-thawed sperm quality (Fair, Doyle, Diskin, Hennessy, & Kenny, 2014). Studies with rams, bulls, fowl, goat and boars have suggested benefits after dietary supplementation of PUFAs on male reproductive parameters (Blesbois, Douard, Germain, Boniface, & Pellet, 2004;Dolatpanah, Towhidi, Farshad, Rashidi, & Rezayazdi, 2008;Estienne, Harper, & Crawford, 2008;Gholami et al, 2010;Rooke et al, 2001;Samadian et al, 2010;Selvaraju et al, 2012;Surai et al, 2000), whereas other studies in rams, humans, turkeys, chickens, rabbits and boars failed to show any significant effect on semen quality (Castellano et al, 2010;Cerolini, Zaniboni, Maldjian, & Gliozzi, 2006;Conquer, Martin, Tummon, Watson, & Tekpetey, 2000;De Graaf, Peake, Maxwell, O'Brien, & Evans, 2007;Gliozzi et al, 2009;Paulenz, Taugbøl, Hofmo, & Saarem, 1995;Zaniboni, Rizzi, & Cerolini, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Quando caprinos foram alimentados com óleo de peixe, não foi encontrada diferença significativa para integridade de membrana plasmática, avaliada pelo teste de coloração com eosina-nigrosina (DOLATPANAH et al, 2008). Contudo, há relato de que a porcentagem de espermatozoides com membrana plasmática íntegra mensurada pelo HOST foi superior no sêmen descongelado, quando búfalos foram alimentados com óleo ou semente de girassol (ADEEL et al, 2009).…”
Section: Pi_h342 (%) E_n (%)unclassified